2016
DOI: 10.1002/cncr.30025
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between coping strategies, quality of life, and mood in patients with incurable cancer

Abstract: Background Patients with incurable cancer face many physical and emotional stressors, yet little is known about their coping strategies or the relationship between their coping strategies, quality of life (QOL) and mood. Methods As part of a randomized trial of palliative care, this study assessed baseline QOL (Functional Assessment of Cancer Therapy–General), mood (Hospital Anxiety and Depression Scale), and coping (Brief COPE) in patients within 8 weeks of a diagnosis of incurable lung or gastrointestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
191
1
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 203 publications
(224 citation statements)
references
References 53 publications
(105 reference statements)
17
191
1
15
Order By: Relevance
“…Previous studies showed that the educational level and professional status might be associated with some specific coping strategies [4042]. Associations between coping strategies and quality of life were elsewhere documented in other pathologic contexts [33, 43]. We found positive correlations between the positive thinking coping strategy and QoL dimensions, physical-like dimensions but particularly mental-like dimensions.…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies showed that the educational level and professional status might be associated with some specific coping strategies [4042]. Associations between coping strategies and quality of life were elsewhere documented in other pathologic contexts [33, 43]. We found positive correlations between the positive thinking coping strategy and QoL dimensions, physical-like dimensions but particularly mental-like dimensions.…”
Section: Discussionsupporting
confidence: 73%
“…Emotional support and acceptance correlated with better QOL and mood. Denial and self-blame correlated with worse QOL and mood [32].…”
Section: Discussionmentioning
confidence: 91%
“…The use of emotional support and acceptance strategies was correlated with a better quality of life in that research 24 .…”
Section: Discussionmentioning
confidence: 63%